The Investment Performance of MESDAQ Market Initial Public Offerings (IPOs) - Nurwati A. Ahmad-Zaluki; Lim Boon Kect (Asian Academy of Management Journal of Accounting and Finance, 2012)
This study provides evidence on both the short-run and long-run investment performance of Malaysian initial public offering (IPO) companies that are listed on the MESDAQ Market. The factors that influence the performance are also investigated. In line with past Malaysian studies, the results of the raw and market-adjusted initial returns show that IPO companies are significantly underpriced in the short-run. However, in the long-run, both the CAR and the BHAR methods reveal that these companies underperform the market. Our results concerning the long-run performance contrast with the results observed by previous Malaysian studies using a sample of companies listed on the Main Board and/or the Second Board. However, they are consistent with the results reported in other countries. We find that companies in the technology sector, issued in a hot issue period and underpriced IPO, perform less well in the long-run, which supports the fad hypothesis of long-run underperformance. Our results suggest that investors who purchase IPO shares on the MESDAQ Market gain high positive returns in the short-run but do not fare well in the long-run. This study provides new information to investors when choosing IPOs listed on Bursa Malaysia.